Cardiac tissue engineering: an emerging approach to the treatment of heart failure - Rayat Pisheh, Hossein; Nojabaei, Fatemeh Sadat; Darvishi, Ahmad; Rayat Pisheh, Ali; Sani, Mahsa (Frontiers in Bioengineering and Biotechnology, 2024)
Heart failure is a major health problem in which the heart is unable to pump enough blood to meet the body's needs. It is a progressive disease that becomes more severe over time and can be caused by a variety of factors, including heart attack, cardiomyopathy and heart valve disease. There are various methods to cure this disease, which has many complications and risks. The advancement of knowledge and technology has proposed new methods for many diseases. One of the promising new treatments for heart failure is tissue engineering. Tissue engineering is a field of research that aims to create living tissues and organs to replace damaged or diseased tissue. The goal of tissue engineering in heart failure is to improve cardiac function and reduce the need for heart transplantation. This can be done using the three important principles of cells, biomaterials and signals to improve function or replace heart tissue. The techniques for using cells and biomaterials such as electrospinning, hydrogel synthesis, decellularization, etc. are diverse. Treating heart failure through tissue engineering is still under development and research, but it is hoped that there will be no transplants or invasive surgeries in the near future. In this study, based on the most important research in recent years, we will examine the power of tissue engineering in the treatment of heart failure.